Pengembangan Buku Penuntun Praktikum Sistem Gerak pada Manusia dengan Model Argument-Driven Inquiry (ADI) - Uun Febriyani; Neni Hasnunidah; Rini Rita T. Marpaung (Universitas Lampung, 2018)
This study aims to describe the characteristics, validity, and practicality of the practical guidebook Humans Motion System using ADI model. The research design used was R D with 4D models (define, design, develop, and disseminate), but disseminate stage was not done. The developed product was made with brightly colored drawing envelopes with the letter Book Antiqua font 12. Each practicum guide consists of lab work titles, preliminary theories, objectives, research questions, tools and materials, work steps, argumentation production, argumentation sessions, and reports. The results showed that the validation of experts and practitioners categorized